2019
DOI: 10.1016/j.lfs.2019.116947
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen-mediated potential inhibition of biofilm development and quorum sensing in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is one of the leading causes of opportunistic and hospital-acquired infections worldwide. The infection with P. aeruginosa is frequently linked with clinical treatment difficulties given drug resistance and abuse of antibiotics. Ibuprofen, a widely used non-steroidal anti-inflammatory drug, has been previously reported to exert antimicrobial activity, although the specific mechanism of its action requires additional investigation. Given the regulation effects on quorum sensing (QS), we h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 48 publications
2
39
0
2
Order By: Relevance
“…In recent times, compounds currently used for the treatment of noninfectious diseases as potential antimicrobial alternatives have also been reviewed (Lagadinou et al, 2020;Zimmermann & Curtis, 2017). One example is Ibuprofen, a nonsteroidal anti-inflammatory drug (NSAID) widely used for relief of pain, fever and inflammation, which has demonstrated novel pharmacological actions against bacteria (Dai et al, 2019;Obad et al, 2015;Shah et al, 2018), fungi (Ogundeji et al, 2016;Sanyal et al, 1993) and viruses (Pan et al, 2018;Veljkovic et al, 2015). Interestingly, a short time ago, it was reported a nebulizable formulation of sodium Ibuprofen in high ionic strength with bactericidal properties for the treatment of respiratory infections of fibrotic patients (Muñoz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, compounds currently used for the treatment of noninfectious diseases as potential antimicrobial alternatives have also been reviewed (Lagadinou et al, 2020;Zimmermann & Curtis, 2017). One example is Ibuprofen, a nonsteroidal anti-inflammatory drug (NSAID) widely used for relief of pain, fever and inflammation, which has demonstrated novel pharmacological actions against bacteria (Dai et al, 2019;Obad et al, 2015;Shah et al, 2018), fungi (Ogundeji et al, 2016;Sanyal et al, 1993) and viruses (Pan et al, 2018;Veljkovic et al, 2015). Interestingly, a short time ago, it was reported a nebulizable formulation of sodium Ibuprofen in high ionic strength with bactericidal properties for the treatment of respiratory infections of fibrotic patients (Muñoz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, azithromycin interferes with QS, reducing gene expression and the production of autoinducers in Pseudomonas aeruginosa, while streptomycin does so in Acinetobacter baumannii (Nalca et al, 2006;Saroj and Rather, 2013). Interestingly, this phenomenon has also been identified in drugs of mass consumption such as aspirin (El-Mowafy et al, 2014) and ibuprofen (Dai et al, 2019), in fermented products, and in various bactericidal phytochemicals (Muñoz-Cazares et al, 2017). Thus, the effect of metabolites at low concentrations on microbial social networks and virulence regulation is a frontier issue that increases the number of molecules to be explored at sub-inhibitory concentrations (Figure 1).…”
Section: Anti-virulence Properties Of Bactericidal Phytochemicalsmentioning
confidence: 99%
“…Unfortunately, many common community-acquired pathogenic bacteria, such as Escherichia coli, Klebsiella pneumoniae, Salmonella , methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa , have shown progressive resistance to conventional drugs. A World Health Organisation (WHO) report in 2019 concluded that if the current trend is not averted drug-resistant diseases could lead to the death of 10 million people each year by 2050 (Raymond and Powell 2019; Dai et al . 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As such, interference of the QS system in pathogenic bacteria represents an attractive target for the development of novel therapeutics. For instance, the use of small molecules as potential inhibitors against QS mediated genes responsible for virulence determinants and biofilm formation is an effective strategy in combating microbial resistance to conventional antibiotics (Dai et al . 2019).…”
Section: Introductionmentioning
confidence: 99%